Fetal dystocia in guinea pigs: A case report - de Andrade, Julia Penna; Miranda, Sabrina de Morais; Soares, Camilla Faria; Castanheira, Thaís Larissa Lourenço; Ferrante, Bruno; de Carvalho, Marcelo Pires Nogueira (Brazilian Journal of Veterinary Medicine, 2024)
Dystocia is a common complication in guinea pig pregnancies, presenting significant challenges in clinical management. The present case report describes the presentation, diagnosis, and surgical intervention in an 8 months old female guinea pig with dystocia. The subject is a primiparous guinea pig originating from a commercial breeder, exhibited prolonged labor with two pups, one of which was stillborn. Physical examination revealed a distended abdomen, lack of uterine contractions, signs of distress, and vulvar discharge. Radiographic and ultrasound tests confirmed obstruction due to large fetal size and mineralization of the pubic symphysis. Surgical intervention proceeded with a ventral midline approach, ovariohysterectomy and removal of three fetuses. The guinea pig recovered well from the procedure, being discharged with postoperative care, and the use of anti-inflammatory, analgesics, prokinetics, antibiotics as well as scopolamine. The objective of the present work is to discuss and emphasize the importance of veterinary intervention, diagnostic evaluation and therapeutics for the multifactorial nature of dystocia management. Despite the surgical treatment, the prognosis for both dam and offspring remains guarded, highlighting the need for early detection and intervention to optimize outcomes in guinea pig dystocia cases.